Intratympanic Steroid Treatments May Improve Hearing via Ion Homeostasis Alterations and Not Immune Suppression. Issue 6 (July 2015) - MacArthur, Carol; Hausman, Fran; Kempton, Beth; Trune, Dennis R.
Abstract : Hypothesis: The inner ear (IE) endothelium is capable of responding to therapeutic steroids by altering the local expression of cytokine and ion homeostasis genes that impact inflammation and fluid regulation. Background: Glucocorticoids are often given transtympanically for hearing disorders because of their anti-inflammatory effects, but their direct impact on IE ion homeostasis and cytokine gene expression has not been studied. Methods: The middle ears of Balb/c mice were transtympanically injected with 5 μL of phosphate-buffered saline, prednisolone (Pred), or dexamethasone (Dex). Untreated mice were used as controls. Mice were euthanized at 6, 24, and 72 hours; the cochleas were harvested; and total RNA was isolated from the IE tissues. Expression of eight cytokine genes and 24 ion homeostasis genes was analyzed with quantitative real time reverse transcription polymerase chain reaction. Results: Phosphate-buffered saline caused upregulation of inflammatory cytokine genes that peaked at 6 hours. Surprisingly, Pred and Dex also caused upregulation of most cytokine genes. Interestingly, ion homeostasis genes were predominantly upregulated with Dex and Pred, with Pred having a larger effect. Conclusion: In the murine model, intratympanic steroids caused an initial upregulation of inflammatory cytokine genes in the IE, as well as predominant upregulation of ion homeostasis genes. These findings suggest that glucocorticoids do not suppress IE inflammation but rather cause an initial inflammatory response in the IE. Thus, inflammatory gene suppression is not a likely mechanism for their hearing restorative effects. On the other hand, these steroids have a significant mineralocorticoid function, as demonstrated by increased function of ion homeostasis genes, implicating their ionic and fluid regulatory properties as a mechanism for their therapeutic effects.